REFLECTIONS OF DR. B.R AMBEDKAR’S IDEA OF SOCIAL JUSTICE - Ahmad Lone, Shabir (RADJA PUBLIKA, 2022)
Dr. B. R. Ambedkar is revered as a hero for his role in advancing equality. Bhimrao Ramji Ambedkar was an instrumental figure in the formation of our nation's constitution and was one of the principal authors of it. He made it illegal to discriminate against those who were considered to be of a lower caste or to be untouchable, and he worked toward establishing equality among the citizens of our nation. He stated that he had faith in a community that could support the ideals of friendship, equality, and fraternity. However, in the early days of our nation, a man who had done so much for our country had been subjected to numerous cruelties because of his caste. Dr. Bhimrao Babasaheb Ramji Ambedkar was a renegade who challenged the social order in which the contradiction of caste and class had been apparent for years. His egalitarian philosophy was